An Analysis of the Future Financial Performance of Fintech Lending in Indonesia - Susanti, Alifi Tria; Kasno, Kasno; Wiyono, Muhammad Wimbo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Peer-to-Peer Lending Fintech is a digital-based business model that facilitates lending transactions between financial intermediaries. This form of fintech is primarily targeted at small and medium-sized enterprises (SMEs) that find traditional bank loan requirements to be overly stringent. The objective of this study is to examine the financial performance of peer-to-peer (P2P) lending fintech in Indonesia. This research employs a quantitative approach, utilizing the ARIMA method to forecast the financial performance of fintech lending in the country. The ARIMA method involves model identification, parameter estimation, model selection using statistical tests, and forecasting for future data points. The analytical tool used in this study is EViews. The variable analyzed is financial performance, measured by Return on Assets (ROA). The data spans from January 2021 to February 2025, with forecasting conducted for the subsequent 10 months, extending through December 2025. The optimal ARIMA model identified for forecasting the ROA of fintech lending financial performance is ARIMA (2,1,1). The forecasting results indicate an upward trend in ROA over the next 10 months, reaching an estimated increase of up to 22% by December 2025.